1999
DOI: 10.1103/physrevb.60.4731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetoexciton correlations on the coherent emission of semiconductors

Abstract: Mean-field, Hartree-Fock theory has been successful in explaining many nonlinear optical experiments in semiconductors. But recently experiments have shown important cases where the mean-field theory ͑the semiconductor Bloch equations͒ fails. One such case is bulk GaAs in a strong magnetic field. Here the excitonexciton interaction can be tuned by varying the magnetic field, providing an excellent method for studying the transition from a regime where mean-field theory is valid to a regime where exciton-excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…The light holes give rise to higher frequency oscillation with larger amplitude and heavy holes with lower frequency oscillations modulate the light hole signal, giving rise to multiple oscillations. Similar feature was demonstrated experimentally by Kner et al [33] and Albrecht et al [34] in their work on quantum wells. Schmitt-Rink et al [35] and Garro et al [36] reported experimental observation of heavy-and light-hole beating in GaAs/ AlGaAs QWs.…”
Section: Resultssupporting
confidence: 54%
“…The light holes give rise to higher frequency oscillation with larger amplitude and heavy holes with lower frequency oscillations modulate the light hole signal, giving rise to multiple oscillations. Similar feature was demonstrated experimentally by Kner et al [33] and Albrecht et al [34] in their work on quantum wells. Schmitt-Rink et al [35] and Garro et al [36] reported experimental observation of heavy-and light-hole beating in GaAs/ AlGaAs QWs.…”
Section: Resultssupporting
confidence: 54%
“…Thus it is stored in the medium until the second pulse triggers that emission. This`coherent memory' can be interpreted as a non-markovian process involving the 2-particle correlation polarization waves interacting with a bath of 4-particle correlations 36 . The effects of 4-particle correlations have been shown to be important in other recent experiments as well 7 .…”
Section: High-order Correlation Effectsmentioning
confidence: 99%
“…In other systems, such as magnetoexcitons in bulk GaAs, this rise time can become much longer than the decay time. 39,18 Experimentally we found that, in the range of density explored here, the decay time decreases by a factor of 2 following approximately the relation T 2 Ϫ1 ϰN cw 0.15 , see the solid symbols in Fig. 6.…”
Section: ͑16͒mentioning
confidence: 86%